Individualized and small group intervention for grade I readers-at-risk - Fernandez, Razeale Gloria (2005)
The single-subject experimental study combined with group analysis for comparison of gains on performance, developed and implemented a 10-week reading intervention program for Grade One readers-at-risk. The study found that READERS improved - the reading proficiency of the four Grade One readers-at-risk in the book and print awareness, mastery of the alphabet, phonemic awareness, textual read aloud, journal writing and comprehension. It was also discovered that contrary to the conventional belief that one-on-one is the most effective instructional arrangement, this study found no advantage of one-on-one intervention over the group instruction.